1995
DOI: 10.1007/bf00024445
|View full text |Cite
|
Sign up to set email alerts
|

Spatial heterogeneity as a multiscale characteristic of zooplankton community

Abstract: Key words: marine and freshwater zooplankton, spatial heterogeneity, scaling, multiple abiotic and biotic generative processes . AbstractZooplankton spatial heterogeneity has profound effects on understanding and modelling of zooplankton population dynamics and interactions with other planktonic compartments, and consequently, on the structure and function of planktonic ecosystems . On the one hand, zooplankton heterogeneity at spatial and temporal scales of ecological interest is an important focus of aquatic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
123
0

Year Published

2001
2001
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 198 publications
(125 citation statements)
references
References 113 publications
(169 reference statements)
2
123
0
Order By: Relevance
“…Patchiness has long been recognized as a biologically significant trait in plankton ecology (Hardy 1936;Pinel-Alloul 1995), and recently ecological effects of patchiness on different scales have received increasing attention, in particular with regard to predatorprey relationships (Weimerskirch 2007). Our study indicates that dominating Alle alle prey aggregated in patches with a characteristic length scale of below 1.2 km (Table IV).…”
Section: Resultsmentioning
confidence: 59%
See 1 more Smart Citation
“…Patchiness has long been recognized as a biologically significant trait in plankton ecology (Hardy 1936;Pinel-Alloul 1995), and recently ecological effects of patchiness on different scales have received increasing attention, in particular with regard to predatorprey relationships (Weimerskirch 2007). Our study indicates that dominating Alle alle prey aggregated in patches with a characteristic length scale of below 1.2 km (Table IV).…”
Section: Resultsmentioning
confidence: 59%
“…For this particular potential feeding ground a sampling grid of less than 2 km would be necessary to cover the variation in the area. Given the logistical demands associated with sampling at such resolution, modern high-resolution sampling equipment such as continuous net-plankton pumping (Molinero et al 2008), optical plankton recorder (Pinel-Alloul 1995;Currie et al 1998) and acoustics (ADCP) (Pinel-Alloul 1995;Tokarev et al 1998;Coyle 2000;Hembre & Megard 2003) are necessary complements to traditional plankton net tows. Furthermore, the heterogeneity in horizontal distribution also raises questions about the extent and nature of vertical patchiness.…”
Section: Resultsmentioning
confidence: 99%
“…Field survey has also revealed that above-mentioned stations give maximum success in fishing, which also indicates the availability of resource in this area that supports the cause of clumping of zooplanktons. It has been already established that fine-scale horizontal variability in zooplankton distribution is related to the presence and feeding of planktivorous fish (Pinel-Alloul 1995;Jeppesen et al 1997;Romero et al 2004). In Bakreswar reservoir, clumping of cladocerans and copepods is high in Stations I Index of dispersion is based on sampling units and its size and thus has some limitations in predicting the exact distribution pattern for organisms with continuous distribution.…”
Section: Discussionmentioning
confidence: 99%
“…Although many zooplankton are actively mobile, creating patches over small spatial scales, most zooplankton are considered to be primarily "passive drifters" with respect to large-scale water movement (Pinel-Alloul 1995;Wiafe & Frid 1996). The use of drogues and surface drifters to track water currents is common in marine systems (Wiafe & Frid 1996;Carr & Rossby 2001), and this technique may be transferred to the measurement of currents in other waterbodies.…”
Section: Introductionmentioning
confidence: 99%